Sustainability of urban coastal area management: A case study on Cide - Cetin, Mehmet (Informa UK Limited, 2016)
ABSTRACTThe coast along an urban area, when it is healthy, can play a role in the city, affecting the urban identity, enriching the visual aspects of life there, and overall affecting the quality of life in a positive way. Management and planning recommendations for the coast of Cide are presented. Cide is feeling the effects of rapid changes in land use. Studies conducted with geographic information systems (GISs) in order to analyze this process have shown that the natural structure of the user area of a coast changes over time. In particular, change manifests itself in an increase in construction, forests, and people living there. As for coastal planning, research priorities in the Cide coastal area, including some external environmental factors such as the social and economic factors affecting coastal development, were investigated. A method based on land use classification has been developed in the GIS environment. The data were supported by surveys conducted with residents. Based on the GIS results,...
Keywords: 13. Climate action; 11. Sustainability; 14. Life underwater; 15. Life on land; 12. Responsible consumption